Leukocytoclastic vasculitis associated with sorafenib treatment for hepatocellular carcinoma. Issue 1 (January 2020) - Prejac, Juraj; Kekez, Domina; Belev, Borislav; Kocić, Lidija; Bulimbašić, Stela; Pleština, Stjepko
Abstract : Small-vessel vasculitis is an uncommon diagnosis associated with many causes, including certain medication. Characteristic findings are immune complex deposition, vessel wall damage, and erythrocyte extravasation. We present a case of a 77-year-old man with advanced hepatocellular carcinoma who was treated with sorafenib. Twenty days post introduction to sorafenib, the patient experienced high fever and painful purpura on the lower limbs. The results of the skin biopsy confirmed the diagnosis. More extensive diagnostics was undertaken, which excluded other possible causes of vasculitis and infectious disease. Following a full recovery, after the steroid treatment was completed, sorafenib has been continued until the progression of the carcinoma. This is the second described case of hepatocellular carcinoma associated with sorafenib treatment and leukocytoclastic vasculitis. Sorafenib is a potential cause of vasculitis, and clinicians should bear in mind to differentiate it from hand-foot skin reaction, which is a common side effect of multikinase inhibitors. The result of our assessment is important considering that vasculitis requires more specific diagnostic procedures, treatment, and often drug discontinuation.